A study of land utilisational and region developemental questiones in Székelyföld - Ambrus, Tünde (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
Székelyföld is a territory where the natural and social geofactors’ complexity have combined to bring a specific potential of the land in the special configuration of the Carpathian Basin, on the Eastern periphery of Transylvania, and the central and Southern parts of the Eastern Carpathian Mountains. Documenting the potential of Székelyföld’s land and spa traditions makes it clear that it is extremely important to rediscover the utilisation of the land based on the natural resources, and that subsequent development based on natural values is a strategically important issue. Therefore, I argue that giving priority for developing such tourism, that provides a new solution to rational land utilisation while also taking into account the special characteristics due to regional affiliations, natural resources and demand trends is of vital importance. In this study I examine the natural requirements (hydrological and geological resources) that constitute the base of health and spa tourism, also the infrastructure which will possibly receive support from the pre-accession funds of the European Union and the various programmes for financing and expansion possibilities to promote rural development. Based on these investigations I put forward proposals to avoid negative effects, and also suggest some measures that reflect the geographer’s approach that should be applied in the organisation of tourism. We should consider that badly planned, taught and managed tourism endangers the same resources that it is based upon.
Keywords: region; land utilization; health tourism; mineral water (‘borvíz’); mofetta; region development; subsidy programmes